2012
DOI: 10.1074/jbc.m112.404400
|View full text |Cite
|
Sign up to set email alerts
|

Francisella DnaK Inhibits Tissue-nonspecific Alkaline Phosphatase

Abstract: Background:Pulmonary Francisella infection resulted in reduction of plasma alkaline phosphatase activity. Results: Francisella heat shock protein DnaK binds to alkaline phosphatase thus reducing enzymatic activity. Conclusion: A Francisella protein component responsible for alkaline phosphatase inhibition was identified. Significance: We present a novel mechanism used by a bacterial pathogen to evade the host's defense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Some newly synthesized proteins require posttranslational ATP-dependent folding, which is performed by the chaperones of the HSP family. Previously, it has been shown that chaperones of HSP families are not only important for Francisella biology but also affect the host immune response through participation in pathogenesis , and intracellular survival within the host cell . The Francisella genome encodes 9 HSP families, many of which were identified as responders to heat shock and oxidative stress .…”
Section: Resultsmentioning
confidence: 99%
“…Some newly synthesized proteins require posttranslational ATP-dependent folding, which is performed by the chaperones of the HSP family. Previously, it has been shown that chaperones of HSP families are not only important for Francisella biology but also affect the host immune response through participation in pathogenesis , and intracellular survival within the host cell . The Francisella genome encodes 9 HSP families, many of which were identified as responders to heat shock and oxidative stress .…”
Section: Resultsmentioning
confidence: 99%